Test Bench Concept for Testing of Gripper Properties in a Robotic Palletizing Process - Jarosław PANASIUK; Jarosław PANASIUK (Koncepcja stanowiska do badania własności chwytaków w zrobotyzowanym procesie paletyzacji, 2022)
Palletizing and depalletizing processes require specialized equipment, such as grippers dedicated to the type and dimensions of the goods to be handled. The traditional approach used in the robotisation of palletizing workstations is therefore mainly based on the development of specialized grippers, whose design limits their use in other applications. The article presents a concept of a modular gripper system enabling palletization of goods in collective packaging, including cartons, shrink-wrap packs, and bags. The concept developed involves the construction of a gripper system based on common modules that provide for extensive parameterization of device operation. The authors also propose a test bench to test the properties of grippers in a robotic palletizing process.
Keywords: Zrobotyzowany proces paletyzacji; Zrobotyzowany proces paletyzacji